A QUALITATIVE APPROACH ON THE RELATIONSHIP BETWEEN WORKFORCE DIVERSITY, JOB SATISFACTION, AND EMPLOYEEE PERFORMANCE AT KPP PRATAMA MANADO - Kusumawati, Windy .; Saerang, David P.E; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Â Abstract: Humans are always actives role in all activities inside the organization. The purpose of the company will be impossible to achieve without active participation. KPP Pratama is the one of the cAompany yang has many employees from various regions in Indonesia, which is KPP Pratama Manado rich in the characteristics of each employee. The research aims to examine analyze the influence of workforce diversity, job satisfaction, and employee performance at KPP Pratama Manado. Data was collected through the interview individually. This research utilizes a qualitative approach to examine and explore in-depth interview on their experiences and opinion. As the final result of the research, shows that workforce diversity, job satisfaction and employee performance have a positive influence. Can be seen from the following factors there are age, culture, education background, religion, gender, pay, supervisor, co-worker, the work itself, planning, and developing which makes employee comfortable and give good performance to company. The organization should pay more attention to the division of employee in each department so that the gap of age and performance in each department could be managed accordingly, so as to minimize the problems that exist within the organization.Keywords: human resource management, workforce diversity, job satisfaction, employee performance